2006
DOI: 10.1529/biophysj.105.076331
|View full text |Cite|
|
Sign up to set email alerts
|

Lateral Diffusion Anisotropy and Membrane Lipid/Skeleton Interaction in Outer Hair Cells

Abstract: The organization of the plasma membrane of cells in lipid domains affects the way the membrane interacts with the underlying protein skeleton, which in turn affects the lateral mobility of lipid and protein molecules in the membrane. Membrane fluidity properties can be monitored by various approaches, the most versatile of which is fluorescence recovery after photobleaching (FRAP). We extended previous FRAP experiments on isolated cochlear outer hair cells (OHCs) by analyzing the two-dimensional pattern of lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 67 publications
(100 reference statements)
2
21
0
Order By: Relevance
“…Our FRAP protocol for measuring di-8-ANEPPS lateral mobility in the OHC produced D values that were comparable to those reported in other studies of di-8-ANEPPS diffusion in OHCs (Oghalai et al 1999(Oghalai et al , 2000de Monvel et al 2006;Chen and Zhao 2007). Although our effective diffusion coefficients were somewhat larger, we attribute this to differences in experimental setup, diffusion models, and fitting routines, since our reported D values for di-8-ANEPPS diffusion in HEKs and OHCs were similar.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our FRAP protocol for measuring di-8-ANEPPS lateral mobility in the OHC produced D values that were comparable to those reported in other studies of di-8-ANEPPS diffusion in OHCs (Oghalai et al 1999(Oghalai et al , 2000de Monvel et al 2006;Chen and Zhao 2007). Although our effective diffusion coefficients were somewhat larger, we attribute this to differences in experimental setup, diffusion models, and fitting routines, since our reported D values for di-8-ANEPPS diffusion in HEKs and OHCs were similar.…”
Section: Discussionsupporting
confidence: 86%
“…Previous work has measured lateral diffusion in OHCs using FRAP and demonstrated that the fluidity of the OHC plasma membrane is similar to other eukaryotic cells (Oghalai et al 1999(Oghalai et al , 2000de Monvel et al 2006). Interestingly, lipid lateral mobility in OHCs has been reported to be both voltage-and tension-dependent (Oghalai et al 2000).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations